Self-assembly of solid nanoclusters in molybdenum under gas ion implantation. (15th March 2021) - Sun, Cheng; Jiang, Chao; Jossou, Ericmoore; Topsakal, Mehmet; Gill, Simerjeet K.; Ecker, Lynne E.; Gan, Jian
Abstract: The self-assembly of defects in materials could create unique physical and chemical properties. In nuclear fuels, the formation of self-assembled fission products mitigates fission-gas-release and swelling. Here we report the formation of a solid nanocluster superlattice in molybdenum, an important constituent in metallic fuels, under krypton gas ion implantation. X-ray absorption near edge structure measurements coupled with density functional theory calculations show that the pressure of krypton nanoclusters in molybdenum is 2 GPa and molecular dynamic simulations reveal that the krypton atoms are solid in the nanoclusters with a krypton-to-vacancy ratio of 0.28 at 300 K. Graphical abstract: Image, graphical abstract